Waking During Pregnancy: Literature Review - Othman, Mohammad; Othman, Salah M. (British Journal of Healthcare and Medical Research, 2022)
There is no agreement among researchers whether exercise is salutary during pregnancy. Utmost studies report that physical activity poses no trouble to either pregnant woman or her fetus. On the other hand, walking is the most generally chosen type of physical activity during pregnancy where it provides several health benefits to the lady and her baby. Standard quest procedures were followed to determine sources from the literature specific to walking during pregnancy for use in this review. Included studies were presented narratively, and appraisal of their methodological quality was conducted using the Jadad quality assessment tool. Walking found to be useful in easing gravidity- related pain and psychological symptoms and reducing gestational weight gain. Nevertheless, inconsistencies in findings between studies hamper the delineation of establishment conclusions on these ultimate issues. Overall, studies demonstrated a positive effect of physical exertion interventions on the well- being and physical and psychological health of pregnant women. Future studies are encouraged and advised to utilise well recognised assessment tools. Community and antenatal health programs advocated to recommend physical activity and exercise during pregnancy.